Heterologous recombinant protein with decapacitating activity prevents and reverts cryodamage in ram sperm: An emerging biotechnological tool for cryobiology - Zalazar, Lucía; Ledesma, Alba Verónica; Hozbor, Federico Andres; Cesari, Andreína (Elsevier, 2019)
During the last decades fundamental and applied aspects of mammalian ram sperm cryopreservation have been increasingly explored by scientists and biotechnologists. Many works report modifications in the composition of the freezing extenders and explore the beneficial and detrimental effects of seminal plasma or seminal plasma components in cryopreservation. Seminal plasma is known to contain stabilizing proteins, thereby this is a good start point to study the maintenance of membrane stability based on the basic knowledge of sperm physiology. However, seminal plasma composition is variable among rams and also the introduction of exogenous seminal plasma or its fractions to commercial semen can be associated with the transmission of viral diseases. Our work shows that a mouse protein, called SPINK3 (Serine Protease Inhibitor Kazal type 3) with decapacitating activity interacts with heterologous ram sperm when it is produced as a recombinant molecule. By immunocytochemistry assays we demonstrate that this protein (naturally expressed by mouse seminal vesicle under androgenic control) binds to the apical portion of both fresh and frozen ram sperm, the same localization described in mouse homologous sperm. Furthermore, it significantly improves sperm progressive motility compared to non-treated samples when it is added to freezing extenders and to dilution media after thawing. On the contrary, addition of SPINK3 does not modify sperm viability. The percentage of sperm with intact acrosome after ionophore induction was also significantly higher in sperm frozen in the presence of SPINK3 compared to control samples and the addition of SPINK3 after thawing significantly reduced both induced and non induced acrosomal loss, indicating that heterologous SPINK3 might act as a calcium inhibitor transport as described in mouse. Based on our results SPINK3 may find a place as a desirable biotechnological tool to achieve a higher proportion of competent sperm to fertilize.